Credit default swap auctions - Jean Helwege; Samuel Maurer; Asani Sarkar; Yuan Wang (Federal Reserve Bank of New York, 2009)
The rapid growth of the credit default swap (CDS) market and the increased number of defaults in recent years have led to major changes in the way CDS contracts are settled when default occurs. Auctions are increasingly the mechanism used to settle these contracts, replacing physical transfers of defaulted bonds between CDS sellers and buyers. Indeed, auctions will become a standard feature of all recent CDS contracts from now on. In this paper, we examine all of the CDS auctions conducted to date and evaluate their efficacy by comparing the auction outcomes to prices of the underlying bonds in the secondary market. The auctions appear to have served their purpose, as we find no evidence of inefficiency in the process: Participation is high, open interest is low, and the auction prices are close to the prices observed in the bond market before and after each auction has occurred. We qualify our conclusions by noting that relatively few auctions have taken place thus far.
Keywords: G10; G13; G33; 330; Credit default swaps; settlement; auctions; recovery basis; corporate bonds; default